Identifikasi dan Gambaran Pengetahun Pedangang Bakso tentang Formalin - Harleli Harleli; Irma Irma (Jurnal Kendari Kesehatan Masyarakat, 2024)
Unsafe food can endanger health, both for children and adults. As a food additive, formalin is widespread and is often used in snack foods. The aim of this research is to identify formaldehyde and determine knowledge about formaldehyde in food. This research is descriptive in nature with a total sampling technique of 10 meatball sellers at the Famous Bakso Stall in Kendari City. Samples were tested at the Biomolecular Laboratory, Faculty of Mathematics and Natural Sciences, Halu Oleo University. The results of the examination showed that sample 1 was negative for formalin, sample 2 was negative for formalin. Sample 3 was negative for formalin. Sample 4 is negative for formalin, sample 5 is negative for formalin, sample 6 is negative for formalin. Sample 7 was negative for formalin, sample 8 was negative for formalin. Sample 9 was negative for formalin. Sample 10 negative for formalin content. For traders' knowledge constraints, 8 (75%) respondents had sufficient knowledge and 2 respondents (25%) had insufficient knowledge. The conclusion is that meatballs do not indicate the presence of formaldehyde in the sample, to illustrate the knowledge of traders who have sufficient knowledge. Researchers suggest that even though the results of this study are negative, supervision is still needed to ensure compliance with food safety standards